Peculiarities of ukrainian business entering international markets markets under the influence of military risks - T.Yu. Melnyk (Економіка, управління та адміністрування)
Entering foreign markets has become a crucial priority for Ukrainian businesses. Companies are actively exploring opportunities for international expansion to mitigate risks associated with the war and ensure stable operations. The article examines the current trends of Ukrainian businesses entering international markets under martial law conditions. In particular, it analyzes statistical data collected by Ukrainian and foreign organizations, which highlights the growing dynamics of this process. Based on information from the official websites of well-known Ukrainian companies (such as Nova Poshta, Galia Baluvana, Lviv Croissants, Ajax Systems, Rozetka.ua, Farmak, and others) and media publications, the geography of Ukrainian business external expansion is revealed. Additionally, the primary challenges and risks faced by entrepreneurs in launching businesses in European and other countries are identified. Among the most common obstacles are the complexity of legal procedures and the high cost of addressing organizational issues; lengthy registration processes and obtaining all necessary licenses and accounts; difficulties in finding premises for business; protracted procedures for obtaining construction permits; limited access to international capital markets; the need to consider local cultural characteristics and practices, especially in the business environment; and unpreparedness for high taxes and salaries. At the same time, international expansion provides Ukrainian companies not only with resilience under challenging conditions but also with new opportunities. These include access to new markets and customer bases, reduced dependency risks on a single market or product, protection of employees and assets, decreased financial loss risks, increased access to innovative technologies, and enhanced business prestige. Based on an analysis of trends, risks, and advantages, as well as real examples of Ukrainian companies, the article substantiates the key steps in preparing businesses for entering foreign markets. Gradual implementation of these steps will help achieve the set goals and success on the international stage.